Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

In Response to “Toward Balanced Curricula: Advancing Nondiet and Weight-Neutral Education in Dietetics” - Nicholas Slagel; Daniel Hall; Yu Wang; Zoe Duran; Katelyn Crawley; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Emma Laing (Journal of Nutrition Education and Behavior, 2026)

Relationships Between Soil and Vegetation Properties and Soil Carbon Stocks Differ Between Grasslands with Different Water Table Management - Emma M. N. Polman; Kenneth F. Rijsdijk; Perry Cornelissen; Rutger L. van Hall; Franciska T. de Vries (Ecosystems, 2026)
Water table management such as temporal flooding is an important strategy for influencing vegetation development and creating suitable habitat for wildlife in managed wetland systems. Water table fluctuations can also affect soil carbon and nutrient cycling through changes in abiotic soil properties, plant traits and soil microbial communities, but research on the effect of temporal flooding on these relations is limited. Here we tested the hypothesis that winter inundation leads to a plant community with more fast-growth-related plant traits, a bacterial-dominated soil microbial community, and lower soil organic carbon stocks compared to a year-round dry grassland. We compared soil and vegetation of winter-inundated and non-inundated grassland in a Dutch-managed wetland area. In contrast to our hypothesis, we found that winter inundation results in plant communities with more slow-growth-related traits and microbial communities more dominated by fungi, compared to non-inundated grassland. We found no difference between shallow soil organic carbon stocks, carbon-to-nitrogen ratios or nitrogen-to-phosphorous ratios. Winter inundation did, however, change the relationship between soil and vegetation properties and soil carbon stocks, as well as soil nutrient ratios. While soil carbon stocks in non-inundated grassland were explained by abiotic soil and vegetation properties, soil carbon stocks were only explained by microbial properties in winter-inundated grasslands. These findings show that winter inundation can be used for vegetation and wildlife management with limited effects on soil carbon stocks.

Incorporating Nondiet and Weight-Neutral Principles in a University Dietetics Curriculum - Nicholas Slagel; Daniel B. Hall; Yu Wang; Dawn Clifford; Cristen Harris; Jeffrey Hunger; Zoe Duran; Katelyn Crawley; Emma Laing (Journal of Nutrition Education and Behavior, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Combining acoustic telemetry with archival tagging to investigate the spatial dynamic of the understudied pollack, Pollachius pollachius - Marine Gonse; Martial Laurans; Justus Magin; Tina Odaka; Jean‐Marc Delouis; Stéphane Martin; François Garren; Coline Lazard; Mickael Drogou; Thomas Stamp; Peter Davies; Alice Hall; et al. (Journal of Fish Biology, 2025)
Combining fish tracking methods is a promising way of leveraging the strengths of each approach while mitigating their individual weaknesses. Acoustic telemetry provides presence information as the fish move within receiver range, eliminating the need for tag recovery. Archival tags, on the other hand, record environmental variables on tag retrieval, enabling continuous path reconstruction of a fish beyond coastal regions. This study capitalizes on the combination of both methods for geolocating pollack, Pollachius pollachius , an understudied species of the northeast Atlantic, where declining stocks are raising concern. Essential knowledge of population structure and connectivity between essential habitats is critically lacking and could help inform stock assessment and management. The aims of the study were (1) to evaluate the feasibility of double‐tagging pollack, known for being challenging to tag, and (2) to track seasonal movements across the Channel to gain first insights into pollack spatial ecology. In 2022, an extensive network of acoustic receivers was been deployed in the Channel along the French, English, and Belgian coasts as part of the Fish Intel project. We tagged 83 pollack with acoustic transmitters, among which 48 were double‐tagged with data storage tags. Post‐tagging survival assessment, conducted on a subset of 35 individuals, revealed a successful procedure with a 97% short‐term survival rate. By October 2023, the acoustic telemetry network detected 30 out of 83 pollack at least once, with no large‐scale movements observed across the Channel. Presence in the network fluctuates seasonally, peaking in summer, particularly among immature fish. Integrating acoustic detections with temperature and depth time series in a geolocation model enabled trajectory reconstruction of 10 recaptured pollack, seven of which were detected by the network. This combined tracking approach revealed coastal movements along the coast of Brittany in France, highlighting the ecological significance of the Iroise Sea for pollack throughout the year, particularly in summer. The geolocation model also suggested movements towards the entrance of the western Channel. This study highlights the complementarity of acoustic telemetry and archival tagging in reconstructing fish movements in their natural environment. As data accumulate, these innovative tracking methods promise to continually unveil new insights into the spatial ecology of the understudied pollack, which is essential for the species' management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Role of Temperature in the Termination of Dormancy in Zooplankton - Emma Svahn; Marcus Hall; Samuel Hylander (Marine Ecology, 2025)
Organisms in systems with seasonality require adaptations that enable them to endure harsh conditions and to emerge again at an optimal time to start a new period of production. One such adaptation is dormant eggs in zooplankton. While there is much information on the cues leading to the production of dormant eggs, less is known about the termination and hatching of these eggs, especially among marine zooplankton. Our results from a combined laboratory and field study at a coastal Baltic Sea site showed that hatching in some overwintering copepods was temperature‐dependent, with a threshold‐like initiation between 6°C and 9°C. In contrast, overwintering rotifers hatched in comparable abundances in all temperatures, once a similar amount of degree‐days had been accumulated. The field study demonstrated that nauplii started to appear when temperatures increased above 6.8°C and were more abundant close to the sediment than in surface water in early spring, matching the hatching threshold found in the laboratory. Various rotifers increased in abundance at different times during the spring phenology, but without any differences in abundance between deep and surface waters. Hence, the hatching of zooplankton dormant eggs in this system is temperature‐dependent, likely taxa‐specific, and continued climate change is predicted to have implications for the plankton phenology, mismatches, and food web composition.

Restorative function of offshore longline mussel farms with ecological benefits for commercial crustacean species - Thomas Stamp; Simon J. Pittman; Luke A. Holmes; Adam Rees; Benjamin J. Ciotti; Harry Thatcher; Peter Davies; Alice Hall; Georgia Wells; Anna Olczak; Emma V. Sheehan (Science of The Total Environment, 2024)

Get them off the deck: Straightforward interventions increase post-release survival rates of manta and devil rays in tuna purse seine fisheries - Joshua D. Stewart; Melissa R. Cronin; Erick Largacha; Nerea Lezama-Ochoa; Jon Lopez; Martin Hall; Melanie Hutchinson; Emma G. Jones; Malcolm Francis; Maitane Grande; Jefferson Murua; Vanessa Rojo; et al. (Biological Conservation, 2024)

MR Molecular Image Guided Treatment of Pancreatic Cancer with Targeted ECO/miR-200c Nanoparticles in Immunocompetent Mouse Tumor Models - Victoria Laney; Ryan Hall; Xueer Yuan; Emma Hampson; Augusta Halle; Grace Yeung; Kristen-Weber Bonk; Suneel Apte; Jordan Winter; Ruth Keri; Zheng-Rong Lu (Pharmaceutical Research, 2024)
Objective Pancreatic ductal adenocarcinoma (PDAC) is characterized by desmoplasia due to increased deposition of extracellular matrix (ECM) proteins. This work investigates the efficacy of targeted ECO/miR-200c nanoparticles (ELNP) on ECM remodeling in PDAC and tumor proliferation with MR molecular imaging (MRMI) with MT218 in immunocompetent mouse models. Methods The miR-200c mediated regulation of EMT markers was measured in PDAC cells in vitro . Wild-type mice bearing mutated KRAS-driven KPC subcutaneous or orthotopic tumors were dosed weekly with RGD-ELNP/miR-200c at 1 mg-RNA/kg for a total of 4 doses. We utilized MT218-MRMI to non-invasively monitor the alteration of tumor ECM EDN-FN levels by miR-200c and tumor response to the treatment. The changes were also validated by posthumous histopathology. Results Transfection of PDAC cells with ELNP/miR-200c downregulated the expression of FN1 and EDB-FN and some mesenchymal markers, inhibiting 3D spheroid formation and migration of KPC PDAC cells. RGD-ELNP/miR-200c treatment resulted in significant signal reduction in the MT218 enhanced MRMI images of both subcutaneous and orthotopic KPC tumors compared to those prior to treatment and treated with a non-specific control. MT218-MRMI results were suggestive of EDB-FN downregulation in tumors, which was later confirmed by immunohistochemistry. Tumor growth in subcutaneous tumors was significantly attenuated with RGD-ELNP/miR-200c and was an observed trend in orthotopic tumors. Substantial necrosis and remodeling were observed in both models treated with RGD-ELNP/miR-200c based on H&E staining. Conclusion These results demonstrate the feasibility of RGD-ELNP/miR-200c in modulating PDAC ECM and restraining tumor growth and the utility of MT218-MRMI for non-invasively monitoring miR-200c efficacy.

Bycatch and pollution are the main threats for Burmeister's porpoises inhabiting a high-industrialized bay in the Humboldt Current System - Ana M. García-Cegarra; Anna Hall; Emma Martínez-López (Environmental Research, 2024)

A quantitative risk assessment for the incursion of lumpy skin disease virus into Australia via long-distance windborne dispersal of arthropod vectors - Robyn N. Hall; James R. Torpy; Rachel Nye; Emma Zalcman; Brendan D. Cowled (Preventive Veterinary Medicine, 2023)

PFAS surveillance in abiotic matrices within vital aquatic habitats throughout Florida - Emily K. Griffin; Lauren M. Hall; Melynda A. Brown; Arielle Taylor-Manges; Trisha Green; Katherine Suchanec; Bradley T. Furman; Victoria M. Congdon; Sara S. Wilson; Todd Z. Osborne; Shawn Martin; Emma A. Schultz; et al. (Marine Pollution Bulletin, 2023)

The phytotoxicity of soil-applied herbicides is enhanced in the first-year post strategic deep tillage - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Mick Rose; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2023)

Origin and expansion of the world’s most widespread pinniped: Range‐wide population genomics of the harbour seal ( Phoca vitulina ) - Xiaodong Liu; Suzanne Rønhøj Schjøtt; Sandra M. Granquist; Aqqalu Rosing‐Asvid; Rune Dietz; Jonas Teilmann; Anders Galatius; Kristina Cammen; Greg O’Corry‐Crowe; Karin Harding; Tero Härkönen; Ailsa Hall; et al. (Molecular Ecology, 2022)
The harbour seal ( Phoca vitulina ) is the most widely distributed pinniped, occupying a wide variety of habitats and climatic zones across the Northern Hemisphere. Intriguingly, the harbour seal is also one of the most philopatric seals, raising questions as to how it colonized its current range. To shed light on the origin, remarkable range expansion, population structure and genetic diversity of this species, we used genotyping‐by‐sequencing to analyse ~13,500 biallelic single nucleotide polymorphisms from 286 individuals sampled from 22 localities across the species’ range. Our results point to a Northeast Pacific origin of the harbour seal, colonization of the North Atlantic via the Canadian Arctic, and subsequent stepping‐stone range expansions across the North Atlantic from North America to Europe, accompanied by a successive loss of genetic diversity. Our analyses further revealed a deep divergence between modern North Pacific and North Atlantic harbour seals, with finer‐scale genetic structure at regional and local scales consistent with strong philopatry. The study provides new insights into the harbour seal's remarkable ability to colonize and adapt to a wide range of habitats. Furthermore, it has implications for current harbour seal subspecies delineations and highlights the need for international and national red lists and management plans to ensure the protection of genetically and demographically isolated populations.

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Production and diversity of microorganisms associated with sinking particles in the subtropical North Pacific Ocean - Matthew J. Church; Eint Kyi; Robert O. Hall; David M. Karl; Markus Lindh; Alexa Nelson; Emma K. Wear (Limnology and Oceanography, 2021)
Sinking particulate organic matter controls the flux of carbon (C) from the surface ocean to the deep sea. Microorganisms actively colonize particles, but the extent to which microbial metabolism influences particle export remains uncertain. We conducted experiments to quantify rates of bacterial production (derived based on 3 H‐leucine incorporation) and dark C‐fixation (based on 14 C‐bicarbonate assimilation) associated with sinking particles collected from the base of the euphotic zone (175 m) in the subtropical North Pacific Ocean. Seawater was amended with sinking particles and rates of filter size‐fractionated (0.2, 2, and 20 μ m) bacterial production and dark C‐fixation were measured. Sequencing of 16S ribosomal RNA (rRNA) gene amplicons revealed that microorganisms in the particle‐amended treatments differed from those in the unamended seawater controls, with the particle treatments enriched in putative copiotrophic bacteria. The addition of sinking particles increased rates of bacterial production (by 6‐ to 9‐fold), and to a lesser extent dark C‐fixation (by 1.7‐ to 4.6‐fold), relative to unamended controls, with most of the production associated with filter pore sizes μ m. Normalizing production to concentrations of particulate C yielded rates that were statistically indistinguishable between particle‐amended treatments and unamended controls. We then examined possible relationships between sinking particulate C flux attenuation and its supply to the mesopelagic waters, revealing that flux attenuation was positively related to increases in particulate C supply. Together with results from our experiments, we suggest processes that contribute to sinking particle disaggregation both increase flux attenuation and favor microbial mineralization of particle‐derived organic matter.

Decadal shift in foraging strategy of a migratory southern ocean predator - Gideon L. van den Berg; Els Vermeulen; Luciano O. Valenzuela; Martine Bérubé; Andre Ganswindt; Darren R. Gröcke; Grant Hall; Pavel Hulva; Petra Neveceralova; Per J. Palsbøll; Emma L. Carroll (Global Change Biology, 2021)
Rapid anthropogenic environmental change is expected to impact a host of ecological parameters in Southern Ocean ecosystems. Of critical concern are the consequences of these changes on the range of species that show fidelity to migratory destinations, as philopatry is hypothesized to help or hinder adaptation to climate change depending on the circumstances. Many baleen whales show philopatry to feeding grounds and are also capital breeders that meet migratory and reproductive costs through seasonal energy intake. Southern right whales ( Eubalaena australis , SRWs) are capital breeders that have a strong relationship between reproductive output and foraging success. The population dynamics of South Africa's population of SRWs are characterized by two distinct periods: the 1990s, a period of high calving rates; and the late 2010s, a period associated with lowered calving rates. Here we use analyses of stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values from SRW biopsy samples ( n = 122) collected during these two distinct periods to investigate foraging ecology of the South African population of SRWs over a time period coincident with the demographic shift. We show that South African SRWs underwent a dramatic northward shift, and diversification, in foraging strategy from 1990s to 2010s. Bayesian mixing model results suggest that during the 1990s, South African SRWs foraged on prey isotopically similar to South Georgia/Islas Georgias del Sur krill. In contrast, in the 2010s, South African SRWs foraged on prey isotopically consistent with the waters of the Subtropical Convergence, Polar Front and Marion Island. We hypothesize that this shift represents a response to changes in preferred habitat or prey, for example, the decrease in abundance and southward range contraction of Antarctic krill. By linking reproductive decline to changing foraging strategies for the first time in SRWs, we show that altering foraging strategies may not be sufficient to adapt to a changing ocean.

Involving Patients in the Development and Evaluation of an Educational and Training Experiential Intervention (ETEI) to Improve Muscle Invasive Bladder Cancer Treatment Decision-making and Post-operative Self-care: a Mixed Methods Approach - Nihal Mohamed; Tung Ming Leung; Qainat N. Shah; Sailaja Pisipati; Donna L Berry; Emma K. T. Benn; Cheryl T. Lee; Simon Hall; Reza Mehrazin; John Sfakianos (Journal of Cancer Education, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.

Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Afroz S. Mohammad; Jessica I. Griffith; Chris E. Adkins; Neal Shah; Emily Sechrest; Emma L. Dolan; Tori B. Terrell-Hall; Bart S. Hendriks; Helen Lee; Paul R. Lockman (Pharmaceutical Research, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Characterization of passive permeability at the blood–tumor barrier in five preclinical models of brain metastases of breast cancer - Chris E. Adkins; Afroz S. Mohammad; Tori B. Terrell-Hall; Emma L. Dolan; Neal Shah; Emily Sechrest; Jessica Griffith; Paul R. Lockman (Clinical & Experimental Metastasis, 2016)

Metabolism, Gas Exchange, and Carbon Spiraling in Rivers - Robert O. Hall; Jennifer L. Tank; Michelle A. Baker; Emma J. Rosi-Marshall; Erin R. Hotchkiss (Ecosystems, 2016)

Retargeting pre-existing human antibodies to a bacterial pathogen with an alpha-Gal conjugated aptamer - Sascha A. Kristian; John H. Hwang; Bradley Hall; Emma Leire; John Iacomini; Robert Old; Uri Galili; Charles Roberts; Kary B. Mullis; Mike Westby; Victor Nizet (Journal of Molecular Medicine, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Invasion and production of New Zealand mud snails in the Colorado River, Glen Canyon - Wyatt F. Cross; Emma J. Rosi-Marshall; Kathrine E. Behn; Theodore A. Kennedy; Robert O. Hall; A. Elizabeth Fuller; Colden V. Baxter (Biological Invasions, 2010)

Effects of capture stress on free-ranging, reproductively active male Weddell seals - Robert Geoffrey Harcourt; Emma Turner; Ailsa Hall; Joseph R. Waas; Mark Hindell (Journal of Comparative Physiology A, 2010)